Drought Policy, Monitoring and Management in Arid Lands - White, David H (Annals of Arid Zone, 2016)
Climate variability is a feature of many arid and semi-arid lands, though only the most protracted periods without rain can correctly be described as droughts. Protracted droughts lead to pressure being put on vegetation and soils through over-stocking, and on governments to provide food or financial assistance. This paper discusses the evolution of drought policy in Australia and southern Africa, highlighting how people in these areas can become more self-reliant through being proactive rather than reactive in coping with drought. The importance of protecting the natural resource base is also emphasized, so that it can be productive in future years. However, an essential prerequisite to achieving increased self-reliance and to reduce the impact of drought is to put a national drought policy in place, and provide the necessary research and education infrastructure so that farmers, agri-business and rural communities can better anticipate and cope with droughts.